Single-stage management of Charcot neuroarthropathy and osteomyelitis in diabetic patients - alvarez, gonzalo; Randolino, Juan Pablo; Gonzalez, Emanuel David; Gaitan, Laura; Lopez, Valeria (Journal of the Foot & Ankle, 2024)
Objective: Describe our experience treating Charcot neuroarthropathy (CN) coexisting with concurrent bone infection in a single step, treated with external fixation, and report the mid-term radiographic and functional outcomes. Methods: Retrospective case series of patients diagnosed with CN and osteomyelitis treated with a single-step approach consisting of necrotic bone debridement and fusion extended over the affected joints using a circular external fixator with a minimum of 18 months of follow-up. Results: Six patients were evaluated, and three patients achieved excellent results and were able to walk outside their homes. One of them required a below-the-knee amputation due to persistent infection. Two patients had good results according to the Pinzur proposed evaluation scheme. All patients agreed that they would choose the reconstruction process for their deformity over an infrapatellar amputation. Conclusion: We believe the results from our case series apply to the previously published literature on this therapeutic modality. Level of evidence IV; Case series.